TEOLOGI KARISMATIK: Peran Roh Kudus dalam Transformasi Hidup Kristen Menurut Roma 8:9 - Sulviani Sulviani; Yanti, Astriani, Esra Septiani, Ovi Florensa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This study aims to further analyze the role of the Holy Spirit in the transformation of Christian life, with a particular focus on Charismatic theology, referencing Romans 8:9. In the context of Charismatic theology, the Holy Spirit is seen as the primary agent responsible for spiritual renewal and the development of Christian character. Romans 8:9 emphasizes the importance of living in the Spirit rather than in the flesh, which forms the foundation for understanding true life transformation. This study uses a qualitative approach with textual analysis to explore the experiences of individuals and communities involved in the Charismatic movement. The findings show that the experience of the presence and power of the Holy Spirit leads to significant changes in daily life, including moral, social, and spiritual aspects. Moreover, these findings highlight how Charismatic experiences encourage engagement in church missions and social services, creating a positive impact on society. This research is expected to contribute to a deeper understanding of the role of the Holy Spirit in Charismatic theology and its implications for contemporary Christian life